Organization of testing of knowledge on the basis of interesting and creative tasks in the process of forming professional competence of future specialists. (International Journal of Psychosocial Rehabilitation, 2020)
This article explores the issues of increasing students' interest in database science, testing and consolidating their knowledge. Many interactive methods and tools have been developed and much research has been done to increase students' interest in conducting classroom and extra-curricular activities. The process of testing and evaluating students' knowledge is important not only for monitoring the learning process but also for raising their interest in science. Therefore, it is important to pay attention to interactive design, gaming techniques, puzzles and mixed formulas in the preparation of control and knowledge test tasks. Based on this, we have developed and tested a range of database tasks that require a variety of interesting and creative approaches.